A new species of grass-infesting felt scale (Hemiptera: Coccomorpha: Eriococcidae), with descriptions of all life stages and a key to the adult female Acanthococcus Signoret of Florida, U.S.A. - Deeter, Lily A.; Miller, Douglass R.; Powell, Erin C.; Moore, Matthew R. (Zootaxa, 2025)
All life stages (adult female, second-instar female, first-instar crawler, adult male, fourth-instar male pupa, third-instar male prepupa, second-instar male) of a new species of felt scale insect (Hemiptera: Coccomorpha: Eriococcidae), Acanthococcus orzo Deeter, Miller & Powell, sp. nov., on Muhlenbergia capillaris (Lam.) Trin. (Poales: Poaceae) in Florida, USA, are described and illustrated, with notes on ecological associations. The species is diagnosed based on the adult female anal-ring setae, setae on the hind tibia, the absence of microtubular ducts, and the morphology of the enlarged setae. Comparisons are given with similar species for all stages. Diagnoses are given for the adult female and adult male. A diagnostic key to the adult females of Acanthococcus Signoret species of Florida is provided. Analysis of DNA extractions from this new species is also performed and the results produced distinctive COI and 18S data.